Evolution and taxonomic distribution of nonribosomal peptide and polyketide synthases. (June 2008) - Amoutzias, Grigoris D; Van de Peer, Yves; Mossialos, Dimitris
The majority of nonribosomal peptide synthases and type I polyketide synthases are multimodular megasynthases of oligopeptide and polyketide secondary metabolites, respectively. Owing to their multimodular architecture, they synthesize their metabolites in assembly line logic. The ongoing genomic revolution together with the application of computational tools has provided the opportunity to mine the various genomes for these enzymes and identify those organisms that produce many oligopeptide and polyketide metabolites. In addition, scientists have started to comprehend the molecular mechanisms of megasynthase evolution, by duplication, recombination, point mutation and module skipping. This knowledge and computational analyses have been implemented towards predicting the specificity of these megasynthases and the structure of their end products. It is an exciting field, both for gaining deeper insight into their basic molecular mechanisms and exploiting them biotechnologically.